2007
DOI: 10.2478/v10001-007-0016-2
|View full text |Cite
|
Sign up to set email alerts
|

Occupationally-Acquired Noise-Induced Hearing Loss: A Senseless Workplace Hazard

Abstract: Despite a high level of public awareness regarding the importance of hearing preservation and increasingly stringent international occupational health, safety and welfare requirements mandating provision of safer work environments, ONIHL continues to be a significant occupational hazard. ONIHL is permanent and may cause significant disability, for which there currently exists no cure, but is largely overtly-preventable. The impact of ONIHL on the global transition toward dominant communication-rich white-colla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
51
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 47 publications
3
51
0
3
Order By: Relevance
“…The current study successfully identified a specific occupational group with noise exposures in open space for LPG infusion industry, which has never been reported in the in-field of occupational hygiene 2) . Environmental noise measurements presented that the occupational noise exposures for field workers were relatively higher for all the noise indicators.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…The current study successfully identified a specific occupational group with noise exposures in open space for LPG infusion industry, which has never been reported in the in-field of occupational hygiene 2) . Environmental noise measurements presented that the occupational noise exposures for field workers were relatively higher for all the noise indicators.…”
Section: Discussionmentioning
confidence: 92%
“…It is of interest that the habit of frequent tea or coffee consumption was found to eliminate 97% risk of the existence of hearing loss in multivariate analyses. However, no evidence about its molecular mechanism or clinical observation was reported in medical literature 2) . Further investigations on this issue are in need.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hearing protection is often the only practical means of mitigating the effects of noise-induced hearing loss (NIHL) (1,2) . In New Zealand, NIHL is prevalent (3) , however there is also a lack of research and publications that address the issue (3) .…”
Section: Introductionmentioning
confidence: 99%